Analysis of artichoke cultivation in the Andean area of Perú - Quispe Rodríguez, Juan (2019)
The artichoke (Cynara scolymus L.) is an export product with high expectations in our country, basically in the Coast, also in the mountains it has great possibility, in the inter-Andean valleys at altitudes that range from 2500msnm to 3450msnm (agroclimatic strip apparent that gives a higher comparative quality to the product) for the development of this crop, the Ministry of Agriculture and some private institutions have been promoting its cultivation with good results, especially in the Mantaro Valley, then it became widespread in other areas of the country ( Cajamarca, Trujillo, Cuzco, Puno, Arequipa among other areas) The varieties are: Creole (with thorns), green globe and Lorca (without thorns), marketed by producers directly to exporting processing companies such as Danper, SAC Processor , Viru, Agro Mantaro, Talsa, etc., whose boom was in the years from 2010 to 2015, the intervention of financial institutions that support yaron productive projects in the mentioned areas such as USAID and the FIP, favoring mainly small producers in the Andean zone of Peru